Analysis of the Use of AI (Artificial Intelligence) Based Learning Media in State Vocational High Schools (SMK) in Langkat Regency - Sari, Darmaida (Universitas Muhammadiyah Ponorogo, 2025)
The purpose of this study is to determine the extent of the use of AI (Artificial Intelligence) based learning media in Vocational High Schools in Langkat Regency. This is qualitative study with a descriptive approach. There are four State Vocational High Schools (SMK) in Langkat Regency namely SMK Negeri 1 Pematang Jaya, SMK Negeri 1 Serapit, SMK Negeri 1 Tanjung Pura, and SMK Negeri 1 Stabat which are the places of research. Totally there are 20 teachers from four schools became informants in this study. In this study, data collection used is in-depth interviews. The findings of the study show the use of AI in the classroom learning process as a teaching medium is still far from effective. Many teachers have not used AI as their learning media. Most teachers already know about AI generally, but the use of AI in education as a learning medium is still not widely known and implemented. Even some teachers still do not know what AI (Artificial Intelligence) actually is. Supporting facilities and infrastructure such as: Unstable or even lost internet connection, limited WIFI, Projectors, PCs that do not support are some of the reasons why AI is still not effective as a learning medium in the classroom. It is hoped that socialization, workshops and training on the use of AI for teachers can be carried out by the central education office and local education offices to increase awareness of technology.